Peningkatan Keterampilan Masyarakat Desa Kerik Melalui Pembuatan Tas Batik Shibori - Wachidatul Linda Yuhanna; Vivin Kusuma Dewi; Filda Dwi Utami; Alfin Safitri; Indah Ratna Sari; Dherrys Septian Kriswandha; Kuswo Hadi Wiguno (Pakis Journal Institute, 2024)
Kerik Village has one of the leading products, namely bags. The results of observations show that many people in Kerik Village still need side jobs to improve family welfare. So far, the making of bag products is still constrained by several factors, especially related to product design, production, and marketing. The purpose of this community service program training is to improve the skills of the Kerik Village community in making Shibori batik bags. This training was conducted from April to May 2024. The targets of this program were 20 PKK women of Kerik Village. The approach taken from this program is the method of discussion, hands-on practice and evaluation. The community service program in Kerik Village ran conducively and smoothly and produced products in the form of Shibori batik bags. The training participants were able to make Shibori batik bags well. The level of understanding was very good at 15%, good at 75%, quite good at 0% and less good at 0%. In general, the training results showed that the participants understood how to make Shibori batik bags. This training on making Shibori batik bags can support PKK in adding insight, skills, creativity and income in the development of creative industries.